Green synthesis of magnesium oxide nanosheets by using Citrullus colocynthis fruit extract and its use in biofuel production. (December 2022) - Khan, Umar Nawaz; Inayat, Abid; Shah, Ghulam Mujtaba; Hassan, Hassan M.A.; Zaki, Magdi E.A.; Alanazi, Abdulaziz A.; El-Zahhar, Adel A.; Noureen, Shama; Abbas, Syed Mustansar
Abstract: The present study focuses on the novel green synthesis approach of heterogeneous MgO nanocatalyst for biodiesel production from a novel Citrullus colocynthis fruit extract while the tea plant ( Camellia assamica ) is used as a source for oil. The green synthesis method is an environmentally friendly, cost-effective, non-toxic, and easy method yielding high biodiesel synthesis efficiency as compared to a homogenous catalyst. The XRD results confirm the required MgO phase with an average crystallite size of 42.6 nm. A sheet-like porous morphology of MgO in the range of 1–5 nm is observed from FESEM/EDX analysis with a surface area of 147.4 m 2  g −1 and mesopores laying in the range of 20–30 nm as calculated from the BET and BJH analysis, respectively. This novel nanocatalyst showed high conversion efficiency of the green tea seed oil into fatty acid methyl ester (Biodiesel). The GC-MS and FTIR are used to confirm the conversion of tea seed oil into biodiesel. The maximum biodiesel yield of ∼100% was obtained at a temperature of 60 °C, a methanol/oil molar ratio of 6:2, a catalyst content of 6.25 wt%, and a reaction time of 1.5 h. The fuel properties of the produced biodiesel are well within the range of international standards and the fatty acid methyl ester profile confirms its viability and reliability as an alternative fuel source for an internal combustion engine. Highlights: Green synthesis of MgO heterogenous nanocatalyst. Sheet-like porous morphology of MgO with high surface area. A biodiesel yield of 100% was obtained with 6.25 wt% of nanocatalyst. Fuel properties of biodiesel are well within the range of international standards.